Про степове походження індоєвропейців (з приводу книги Девіда Ентоні "Кінь, колесо й мова" 2007) - Клейн, Л.С. (Кам’яна доба України, 2010)
В археологічній індоєвропеїстиці, як і у всякій живій галузі, великі праці зазвичай з’являються з інтервалом у два десятиліття. З часу публікації впливових праць Ренфру й Меллорі (Renfrew 1987; Mallory 1989) минуло два десятиліття, і от з’явилася капітальна праця Девіда Ентоні «Кінь, колесо й мова»: Як вершники бронзової доби зі степів формували сучасний світ (Antony 2007). Стаття містить критичний аналіз нової монографії відомого індоєвропеїста Д. Ентоні, зроблений видатним теоретиком археології Східної Європи Львом Клейном. Since the time of influential works by Renfrew (1987) and Mallory (1989) two decades passed, and really David Anthony’s capital work appeared: The wheel, the horse and language: How Bronze Age riders from the steppes shaped the modern world (2007). The book of more than 500 pages embraces a lot of excellent maps, schemes, pictures and numerical tables. The bibliography contains more than 800 positions, mainly in Russian, Ukrainian and English; there are also German and French works.
Despite the intriguing title suitable for popular scientific book, a solid research is presented here on the problem of Indo-European origins - the classical problem of discussions for linguists, archaeologists, anthropologists, and (since recent time) geneticists.
American author from the University of Pennsylvania is well known both to Indo-European scholars of the world and to archaeologists of Russia, Ukraine and Moldavia. He is known by his printed works, always creative, original, with bold ideas, as well as by his participation in archaeological projects, especially in Volga basin. From among a few hypotheses of Indo-European origins under discussion he has chosen the idea of steppe origin and defends it. This idea was proposed in archaeology by Ernst Wahle, then picked up by Gordon Childe and Maria Gimbutas, and in recent time developed by Jim Mallory. The idea isn’t new as well as argumentation. The stress on horses, riders and charts as distinctive attribute of the culture of Proto-
Indo-Europeans was exaggerated in the literature since long ago (the Eneolithic riding was maintained by V. N. Danilenko and D. N. Telegin, the charts by R. Drews). Yet Anthony has imparted a new life to these old arguments, found new substantiations, introduced new methods.
His work is especially interesting by the fact that he summarized enormous archaeological materials accumulated in the countries of Eastern Europe (Russia, Ukraine, Moldavia, Poland). In addition to
considerations on the ways of how the Indo-European community has been shaped, he has presented to the western reader a detailed survey of the literature and unpublished materials from this region, the results of old excavations and recent expeditions. This all was inaccessible to western archaeologists because of language barrier and of narrow spread of these publications.
The author pictures the crisis of agrarian “Old Europe” in the connection with the climate deterioration when in the advanced Eneolithic the onslaught of the steppe population on Europe took place. This question is elaborated in more details from the same position in the recently published (in Russian) book by Dergachev (2007) On scepters, on horses, on war. Yet Anthony drives IE from the culture of Suvorovo barrows to Anatolia and ascribes to them the building of Troy I. The ch. 12 specifies changes that occurred in the final Eneolithic on the borders with the steppe – in Maikop culture and in the grand Tripolye proto-towns.
For the Bronze Age the author reconstructs in the steppe the life on wheels, and having driven Afanasyevo culture from the Repin culture, treats this as the origins of Tocharians. Then he outlines the areas of separation of western IE languages (including proto-German) from Usatovo culture through the late Funnel beakers
and Corded ware, while the Pit-Grave culture from Hungary impacts the cultures of Bavaria and Austria and creates proto-Celtic languages. The languages that remained in Hungary become proto-Italic – these
are urn field (Urnenfelder) and Villanova culture. The forming of Indo-Iranian languages (Sintashta) happens on the north border of the steppes. Then the integration of the steppe area into a unified system is considered
and the sizing uo follows.
The book has many attractive sides. The survey of the contemporary state of the materials of Neolithis, Eneolithic and Bronze Age of a vast region will be useful not only for western archaeologists. It is simply
invaluable for them. Yet we also have not such survey, in Russian. We are idle and insufficiently bold or (it can be also so said) too careful. Anthony made a colossal work, and his work certainly will not vanish in waste.
I agree with the author in a version of Renfrew’s construction that leads Indo-Europeans from Anatolia together with Early Neolithic, although the reasons of our aversion are different. Anthony stresses the too long period of co-existence of proto-Indo-European language from neolithization till separation (he gives a thousand year for every language). I rest on unreality to lead Indo-European peoples from Anatolia with
migrations – there are no such archaeological cultures.
The picture drawn by Anthony attracts me: Neolithic “Old Europe” with languages possibly of Afro-Asian type, perished, and the Indo-European language has been formed on its border from native languages of the population assimilated and having adopted the Neolithic. However we diverge in the evaluation of possibilities that it was the steppe population on the eastern border of agrarian Europe. It seems to me that
the northern border of agrarian Europe has no less chance to appear the original homeland.
In my opinion the book is very good and useful. I have read it with great benefit for myself. Anthony’s book is good because in it the factual base is presented better than anywhere, and one can follow the author in his inferences, but one can treat the material elaborated by him otherwise. This is the best characteristic of a book on the problem of origins of Indo-Europeans by the present day.